Dynamics of skill acquisition an ecological dynamics approach - Button, Chris 1973-; Seifert, Ludovic; Jia, Yia Chow; Araujo, Duarte; Davids, Keith (Human Kinetics, Inc., 2021)
"This book covers research on coordination and control, as well as skill acquisition and nonlinear pedagogy, and details how coordination patterns are assembled, controlled and acquired. The purpose of this book is to synthesize and elucidate a constraints-led approach to skill acquisition"